A Potential Concomitant Sellar Embryonic Remnant-Associated Collision Tumor: Systematic Review - Wang, Mingdong; Fu, Qianhui; Song, Mingjing; Zhao, Zongmao; Wang, Renzhi; Zhang, John; Ma, Wenbin; Wang, Zhanxiang (Frontiers in Oncology, 2021)
Background Diagnosing the well-known concomitant Rathke’s cleft cyst (RCC) and differentiating it from other sellar lesions are difficult because RCC is and other sellar lesions are closely related and represent a continuum from simple RCCs to more complex lesions. The purpose of this study is to better understand the adeno- and neurohypophysis adjacent to the par intermedia remnants and their role in the origin of the coexistence of these two distinct tumor neoplasias; to assess the incidence in different age groups; to categorize the pathohistological subtype, which can be incorporated in predictive/prognostic models; and finally, to evaluate the current evidence on collision tumors of the sellar embryonic remnant tract in terms of their biological behavior and pathology. Methods Utilizing the PubMed database, data were collected from 1920 to 2019. Information about demographics, clinical characteristics, and age was summarized and analyzed by using univariable and multivariable models. The same cell type was observed regardless of whether the tumor was only one type or mixed types, and their histologic patterns were assessed. Results The incidence rates were similar among patients stratified into three age subgroups: 40–49 years (24.57%), 50–59 years (19.54%), and older than 60 years (22.98%). We found that various types of sellar lesions, namely, squamous metaplasia (SM) + goblet cells (GC) (HR 46.326), foamy macrophages (FM) (HR 39.625), epithelial cells and multinucleated giant cells or cholesterin (EM) (HR 13.195), a cavernous portion of the right internal carotid artery (CP-ICA) (HR 9.427), epithelial cells with ciliated cuboidal (EC-CC) (HR 8.456), were independently associated with RCC pathological status. These divergent AUCs (0.848 for Hypo as RCC, 0.981 for RCC co PA, 0.926 for CD and CP co RCC) and subtypes of PA (HR 4.415, HR 2.286), Hypo (HR 3.310), CD and CP (HR 2.467), EC and DC and PG and SGR (HR 1.068), coexisting with the risk of a comorbid RCC lesion, may reflect the etiologic heterogeneity of coderivation and the different effects of some risk factors on tumor subtypes. Our analyses suggested that the greatest accuracy was observed for the pituitary adenoma subtype, with an AUC of 0.981 (95% confidence interval [CI]: 0.959–1.005), while the poorest accuracy was observed for aneurysms, with an AUC of 0.531 (95% CI: 0.104–0.958). We separately analyzed and confirmed the above results. Sensitivity analysis revealed no evidence of systematic bias due to missing data. Conclusion This study showed that the histopathological changes in patients with sellar embryonic remnant-associated collision tumors showed highly consistent epithelial cell replacement (renewal) (ciliated columnar epithelium to ciliated squamous epithelium to squamous epithelium) or accumulation, and the RCC cyst wall was similar in structure to the tracheobronchial airway epithelium, with progenitor cell characteristics. The collision accuracy between RCC and other tumors (PAs, craniopharyngioma, chordoma, etc.) is different; these characteristics constitute the theoretical basis for the postmigration development of the pharyngeal bursa.